Perkecambahan dan pertumbuhan benih jati (Tectona grandis Linn. f) dalam merespon perbedaan konsentrasi dan perlakuan waktu perendaman benih dalam asam klorida - Rulia Ervina Dewi; Florentina Kusmiyati; Syaiful Anwar (Universitas Lancang Kuning, 2022)
Teak is a wood-producing plant that is in great demand by the community. However, teak seeds are challenging to germinate due to dormancy, so special treatment is needed before planting. This research aimed to determine the effect of hydrochloric acid and soaking time on breaking the dormancy of teak seed to improve its viability. The first factor was the concentration of hydrochloric acid with four treatment levels, i.e., 0 M, 0.5 M, 1 M, and 1.5 M. The second factor was submerging time which was 12, 18, and 24 hours. Parameters observed included the percentage of germination, maximum growth potential, vigor index, germination rate, growth simultaneity, plant height, number of leaves, and wide leaf. The data obtained were analyzed statistically using ANOVA and followed the DMRT test with a level of 5%. The results showed that hydrochloric acid significantly affected the percentage of germination, maximum growth potential, vigor index, germination rate, growth simultaneity, plant height, and width of the leaf. In addition, soaking time treatment had a significant effect on the wide leaf. The research concluded that hydrochloric acid 0.5 M and 12 hours of soaking time increased the growth of teak seed compared to the control by 29.64% on a percentage of germination, 29% on germination rate, and 41.66% on growth simultaneity.